Virtual pedophilia: sex offender profiling and U.S. security culture - Harkins, Gillian (Duke University Press, 2020)
Introduction: Virtual pedophilia -- Monstrous sexuality and vile sovereignty -- Profiling virtuality and pedophilic data -- Informational image and procedural tone -- Capturing the past and the vitality of crime -- Capturing the future and the sexuality of risk -- Conclusion: Exceptional pedophilia and the everyday case.